Plasticity of Porites astreoides Early Life History Stages Suggests Mesophotic Coral Ecosystems Act as Refugia in Bermuda - Goodbody-Gringley, Gretchen; Scucchia, Federica; Ju, Rebecca; Chequer, Alex; Einbinder, Shai; Martinez, Stephane; Nativ, Hagai; Mass, Tali (Frontiers in Marine Science, 2021)
As the devastating impacts of global climate change and local anthropogenic stressors on shallow-water coral reefs are expected to rise, mesophotic coral ecosystems have increasingly been regarded as potential lifeboats for coral survival, providing a source of propagules to replenish shallower reefs. Yet, there is still limited knowledge of the capacity for coral larvae to adjust to light intensities that change with depth. This study elucidates the mechanisms underlying plasticity during early life stages of the coral Porites astreoides that enable survival across broad depth gradients. We examined physiological and morphological variations in larvae from shallow (8–10 m) and mesophotic (45 m) reefs in Bermuda, and evaluated differences in survival, settlement patterns and size among recruits depending on light conditions using a reciprocal ex situ transplantation experiment. Larvae released from mesophotic adults were found to have significantly lower respiration rates and were significantly larger than those derived from shallow adults, indicating higher content of energetic resources and suggesting a greater dispersal potential for mesophotic larvae compared to their shallow counterparts. Additionally, larvae released from mesophotic adults experienced higher settlement success and larger initial spat size compared to larvae from shallow adults, demonstrating a potential connection between parental origin, offspring quality, and recruitment success. Although both shallow and mesophotic larvae exhibited the capacity to survive and settle under reciprocal light conditions, all larvae had higher survival under mesophotic light conditions regardless of parental origin, suggesting that conditions experienced under low light may enable longer larval life, further extending the dispersal period. These results indicate that larvae from mesophotic Porites astreoides colonies are likely capable of reseeding shallow reefs in Bermuda, thereby supporting the Deep Reef Refugia Hypothesis.